Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 48. Beitrag. Coleoptera: Dascillidae, Eubriidae, Helodidae. - Klausnitzer, Bernhard (Contributions to Entomology = Beiträge zur Entomologie, 1966)
The collection of the family Helodidae made by the expedition to Albania by Deutsches Entomologisches Institut plus 1 individual from the Zoological Museum of Berlin (5 individuals of 3 species) and the Albanian Helodidae of the Museum of Natural History in Vienna (28 individuals of 2 species) were studied. Together they amount to 4 species, all of them new in Albania. - Besides the specimens of the family Dascillidae found by the expedition to Albania by Deutsches Entomologisches Institut (13 individuals of 1 species) were studied. Previous publications mention 1 species of the family Eubriidae in Albania. No Eucinetidae are reported.